CURRENT- AND WAVE-GENERATED BEDFORMS ON MIXED SAND-CLAY INTERTIDAL FLATS: A NEW BEDFORM PHASE DIAGRAM AND IMPLICATIONS FOR BED ROUGHNESS AND PRESERVATION POTENTIAL - Baas, Jaco H.; Malarkey, Jonathan; Lichtman, Ian D.; Amoudry, Laurent O.; Thorne, Peter D.; Hope, Julie A.; Peakall, Jeffrey; Paterson, David M.; Bass, Sarah J.; Cooke, Richard D.; Manning, Andrew J.; Parsons, Daniel R.; et al. (Frontiers in Earth Science, 2021)
The effect of bedforms on frictional roughness felt by the overlying flow is crucial to regional modelling of estuaries and coastal seas. Bedforms are also a key marker of palaeoenvironments. Experiments have shown that even modest biotic and abiotic cohesion in sand inhibits bedform formation, modifies bedform size, and slows bedform development, but this has rarely been tested in nature. This study used a comprehensive dataset recorded over a complete spring–neap cycle on an intertidal flat to investigate bedform dynamics controlled by a wide range of wave and current conditions, including wave–current angle and bed cohesion. A detailed picture of different bedform types and their relationship to the flow, be they equilibrium, non-equilibrium, or relict, was captured in a phase diagram that integrates wave-dominated, current-dominated, and combined flow bedforms. This phase diagram incorporates a wider range of flow conditions than previous phase diagrams, including bedforms related to near-orthogonal wave–current angles, e.g. ladderback ripples. Comparison with laboratory-derived phase diagrams indicates that washed-out ripples, lunate interference ripples and upper-stage plane beds replace the subaqueous dune field, which may be a key characteristic of intertidal flats. The field data also provide a means of predicting the bedform dimensions, which can be transferred to other areas and grain sizes. We show that an equation for the prediction of equilibrium bedform size is sufficient to predict the roughness, even though the bedforms are highly variable in character and only in equilibrium with the flow for half the time. Whilst the effect of cohesive clay is limited under active spring conditions, clay does play a role in reducing the bedform dimensions under quiescent neap conditions. We also investigated which combinations of waves, currents, and bed clay contents in the intertidal zone have the highest potential for bedform preservation in the geological record. This shows that combined wave–current bedforms have the lowest and equilibrium current ripples have the highest preservation potential, even in the presence of moderate and storm waves. Hence, the absence of wave ripples and combined-flow bedforms in sedimentary successions cannot be taken as evidence that waves were absent at the time of deposition.